Optimization of Regident Unit Moving SIM Services to Improve Public Services in the Kudus Resort Police - Manggala, Wiranata Raksa (Advances in Police Science Research Journal, 2024)
The Kudus Police Traffic Unit as one of the executors of public services organized by the National Police has an innovation in SIM administration services, namely mobile SIMs. The mobile SIM of the Kudus Police specifically carries out services for SIM extension. In its implementation, which has been running for some time, there are still complaints and complaints that are felt by the community. In writing this final project, the author uses George F. Terry’s POAC management theory, SWOT analysis theory, the mobile driver’s license service concept, and the concept of public service. This final project uses a qualitative approach and uses field research methods. Retrieval of data using interview techniques, observation, and document study. Data analysis techniques using data reduction techniques, data presentation, and drawing conclusions. The results of this study are the implementation of SIM services around the unit Regident in improving public services in the jurisdiction of the Kudus Police is still not optimal because implementation of Mobile SIM services that have not implemented service standards to the maximum. Based on these results, the authors suggest in order to improve mobile SIM services by optimizing services